Analysis of the Effect of Land and Building Tax Results on Regional Original Income and Economic Growth in the West Area, Central Kalimantan Province - Alexandra Hukom; Dedi K. Mihing; Sunaryo Neneng; Johni Sonder (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Land and building tax for rural and urban areas (hereinafter called as PBB-P2 for Pajak Bumi dan Bangunan Perdesaan and Perkotaan) and fees for acquisition of land and building rights (hereinafter called as BPHTB for Bea Perolehan Hak atas Tanah dan Bangunan) turned into regional tax in 2014. The regulation for collecting PBB-P2 and BPHTB can be found in the act no. 28 of 2009. That regency manages PBB-P2 and BPHTB will positively contribute to the Local Own-Source Revenue and Regional Economic Growth. This study was conducted to analyze how the yield of PBB-P2 and BPHTB affects the local own-source revenue and regional economic growth in western region of central Kalimantan province. The method used to analize the data is quantitative method using Path Analysis. The result of this study showed that PBB-P2 and BPHTB have direct positive and significant effects toward the Local Own-Source Revenue and Local Economic Growth. The Local Own-Source Revenue directly has positive and significant effects on Local Economic Growth. PBB-P2 and BPHTB indirectly have positive and significant effects on the Local Economic Growth through Local Own-Source Revenue.